Polish Presidential Election 2015 in the light of first and second order election conception - Peszyński, Wojciech (Political Preferences, 2016)
Among all the elections organized in Poland, presidential ones are not only the most frequently attended by the voters, but also most eagerly investigated by the researchers. However, the studies concerning the importance of this particular voting is not often examined. On the one hand, there are arguments to classify it as first-order election, on the other, for certain reasons they ought to be regarded as second-order.The aim of this article is to answer the question whether 2015 Polish presidential election were of first or rather second-order importance. In his analysis, the author focused on the following issues: personal strategies, programme strategies, the course of the campaign in the traditional and new media, the level of electoral participation and the influence of the election on the course and outcome of the parliamentary campaign. Key words: Polish presidential election 2015, first order election, second order election